The immunological relay race: B cells take antigen by synapse. - Dustin, M; Dustin, L (2001)
T cells, move over. B cells are now reported, in a recent paper in Nature, to have their own immunological synapses with APCs. Only this time the antigen is whole and B cells don't keep it to themselves.